Journalistic treatment of news on violence against women: Design of a style guide - Pablo, Pomares Villegas, Juan; Pascual, Apolaya Sotelo, José (Edelweiss Applied Science and Technology, 2025)
The purpose of this research is to develop a style guide for reporting news related to violence against women. A basic qualitative methodology was employed, with a hermeneutic interpretative approach and a phenomenological and descriptive design. Interviews were conducted with four specialists in the field, five readers, and a content analysis of three Peruvian newspapers (Correo, La República, and Ojo Norte) was carried out. The findings reveal that participants agree on the lack of a clear and coherent regulatory framework in the media for addressing these issues. As a result, there is no style guide in Peru that regulates the treatment of gender-based violence, leaving journalists subject to their own ethical and deontological criteria. The research concludes that the informational treatment faces significant ethical dilemmas, such as revictimization and sensationalism, and although some media outlets attempt to adopt a more professional approach, the absence of clear ethical guidelines undermines the representation of victims and the public's awareness.